Processes discriminating adaptive and maladaptive Internet use among European adolescents highly engaged online - Tzavela, E.C.; Karakitsou, C.; Dreier, M.; Mavromati, F.; Wölfling, K.; Halapi, E.; Macarie, G.; Wójcik, S.; Veldhuis, L.; Tsitsika, A.K. (2015)
Today adolescents are highly engaged online. Contrary to common concern, not all highly engaged adolescents develop maladaptive patterns of internet use. The present qualitative study explored the experiences, patterns and impact of use of 124 adolescents (Mage=16.0) reporting signs of internet addictive behaviors. The focus was to discern adaptive and maladaptive use patterns, which promote or interfere with adolescents' development, respectively. Semi-structured individual interviews were conducted in seven European countries (Greece, Spain, Poland, Germany, Romania, Netherlands and Iceland) and qualitatively analyzed using grounded theory. Considerable variability emerged in the way adolescents satisfied their personal needs online and offline, in the experienced impact from high online engagement and functional value ascribed to the internet, and in the self-regulatory processes underlying use. Variability in these discriminating processes was linked to adaptive or maladaptive adolescent internet use patterns. The emerged processes can provide direction for designing prevention and intervention programs promoting adaptive use. © 2014 The Foundation for Professionals in Services for Adolescents.